“Estudio de factibilidad para la implementación de una empresa productora de cargadores solares para celulares y su comercialización en la ciudad de Loja, provincia de Loja - Huiracocha Sánchez, Bryan Marcelo (2016)
The present research work consisted in the elaboration of a "Feasibility study for the implementation of a company producing solar cell chargers and its commercialization in the city of Loja, Loja province", to strengthen the local and national business economy. For the execution of the present project specific objectives were proposed that will be of help to carry out each of the pertinent studies in which the existing demand in the city of Loja was determined to begin with the market study and thus determine the Demand and effective supply, determine the capacity used by the company, and establish the legal and administrative organization of the company, and through the financial study will determine the feasibility of this project. The methodology used served to analyze all the information collected, in which the most important technique used was the same survey that was applied to the urban population of Loja in its different districts, which gave us a total of 381 surveys to perform, This helped us to develop the research of the project and to be able to base it with totally reliable bases The market study established the demand and the offer to determine the reception that will have the product in the market, which determined that the effective demand is 48,812 families and the average annual supply is 15,912 mobile phone chargers The originals or the generics. The technical study considered the level of production that the company will have based on its installed capacity which will be 26,280 shippers per year and the capacity used will be 6,240 shippers per year, ie the percentage of capacity used in front To the installed capacity will be of 23.74% of the total, also this study allowed to determine the location, necessary infrastructure, the engineering of the project to carry out it, whereas in the administrative study was determined the constitution of the company, its nature , Corporate name, amount of partners' capital contribution, functional organic structure and function manuals, all of which helped us to implement a good organizational structure for the company. The financial study determined that the amount of investment with which the project began its useful life is $ 21,000.00, which are broken down into a contribution of the capital stock that is $ 11,000.00 or 52.38% of the Total, and an external contribution obtained in the Banco de Loja of $ 10,000.00 representing 47.62% and will be canceled within 5 years at a rate of 15% per annum. In the financial analysis the positive results confirm the feasibility and good profitability of the project, as is the case where the Net Present Value or V.A.N. Gave a value of $ 68,524.84, the Internal Rate of Return or T.I.R. Is 102.68%, the Cost Benefit Ratio or R.B.C. Is $ 1.25, which means that for every dollar invested you will get 25 cents of profit, the Capital Recovery Period or P.R.C. It will be done in 11 months and 20 days, and sensitivity 7 analysis shows that the project will support a maximum cost increase of 15.84% and a maximum revenue decrease of 12.65%. The total value of the investment will be of 19,716.06 dollars and will be financed in its majority by the own capital of the company that is of 11.000,00 dollars and it will be complemented with support of a bank credit of 10,000 dollars made to the bank of Loja. The profit margin proposed by the company will be 24%, which means that the total cost of production of each shipper is $ 19.13 plus the margin will give a retail price of $ 23.73, but the company proposes to work with a sales price adjusted to 24 dollars. With all the above it has been demonstrated that the project in question is feasible and therefore it is recommended to implement the company in the city of Loja. Finally presented the conclusions, recommendation, bibliography and annexes.